PENGARUH KOMPETENSI KEPRIBADIAN DAN KOMPETENSI PROFESIONALITAS GURU KEWIRAUSAHAAN TERHADAP PRESTASI BELAJARSISWAPADA MATA PELAJARAN KEWIRAUSAHAAN DI SMK NEGERI 2 BUNGORO KABUPATEN PANGKEP - ., Maryuni (STKIP Pembangunan Indonesia Makassar, 2017)
This research is a kind of associative research causality is ex-post facto by using quantitative analysis techniques. This research was conducted at SMK Negeri 2 Bungoro. In this study, the population was all students of class X and X TP3 TP1 at SMK Negeri 2 BungoroPangkep enrolled in the academic year 2015/2016 which amounted to 69 people. In this study, the sample used is the number of the population. In this research, creativity and learning styles of data obtained using a questionnaire. While student achievement data is obtained through the value of entrepreneurship subjects contained in grades that have didokementasikan. The data collection was conducted using questionnaires, observation and documentation. The results showed that 1) Simultaneously or together creativity and learning styles positive and significant impact on student achievement in the subjects of entrepreneurship at SMK Negeri 2 BungoroPangkep, 2) learning style is more influential than the creativity of the students' achievement in entrepreneurship subjects at SMK Negeri 2 BungoroPangkep. In this research, creativity and learning styles together affect the dependent variable learning achievement of 13% and the rest influenced by other variables not included in the discussion of this research.Â Â In line with research findings that have been raised, and then in improving student learning outcomes in entrepreneurship subjects at SMK Negeri 2 BungoroPangkep, it is suggested that further enhanced student creativity and learning styles better known for each student so as to improve their academic achievement.Keywords: kreatifitasi, learning styles, student achievement and entrepreneurshipÂ